A predictive model of perceived stress during the first wave of the COVID-19 pandemic in university students Ecuadorians - Reivan Ortiz, Geovanny Genaro; Yanza, Rafael; Campoverde, Ximena; Estrada Cherres, Johanna Paulina; Reinoso García, Lourdes Priscila; Diaz, José; Granero Pérez, Roser (Frontiers in Psychiatry, 2023)
Background and objectives The situation caused by the confinement due to the COVID-19 pandemic and the mobility restriction implemented by governments worldwide had a significant impact on people’s routines. Stressors are known to increase emotional imbalance, uncertainty, and frustration in the general population. This study explores the factors that predispose to the risk of perceived stress from COVID-19 and determines the underlying mediating mechanisms in the Ecuadorian population. Method The cross-sectional study an incidental non-probabilistic sample of n = 977 participating student volunteers from the four regions of the Republic of Ecuador (68.6% women and 31.4% men). Data on emotional regulation (ERQ), perceived stress (PSS), active procrastination (APS), diagnosis and symptoms related to COVID-19, social isolation, coexistence, and a sociodemographic questionnaire (biological sex, marital status, and age) were recruited. Statistical analysis was based on a structural equation model. Results The risk of suffering perceived stress in the COVID-19 pandemic was higher for single women who have lived longer in social isolation, have lived with more people, have poor emotional regulation and high rates of procrastination. This structural model is similar in all Ecuadorian regions χ2 = 21.54 (p = 0.760), RMSEA = 0.001 (95%CI, 0.00–0.02), CFI = 0.998; TLI = 0.999; SRMR = 0.020. Discussion Although our findings are consistent and revealing for the scientific community, the lack of discrimination of the data due to strict isolation measures, taken at different periods by the Ecuadorian government against positive cases of COVID-19, is discussed. The research was applied to the university population, it would be representative to extend the study to schools and colleges. Conclusion We consider this work as a starting point for the creation of preventive models against perceived stress in the university environment in the event of health emergencies.